Ploidy and genome segregation in Musa breeding populations assessed by flow cytometry and randomly amplified polymorphic DNA markers - Oselebe, H.O.; Tenkouano, A.; Pillay, M.; Obi, I.U.; Uguru, M.I. (2006)
The majority of edible bananas (Musa L.) are triploid (2n = 3x = 33) cultivars known as dessert, plantain, or cooking bananas with predominant AAA, AAB, and ABB genomes, justifying the aim of breeding programs to develop improved hybrids of the different utilization classes in the triploid background. This usually involves crossing 3x landraces to 2x accessions that are donors of resistance genes, selecting 4x and 2x primary hybrids from the 3x-2x progenies, and crossing 4x-2x hybrids to produce secondary 3x hybrids. Ploidy and genome segregation routinely occurs during this process and constitutes a major hindrance for selection because this is not easily detectable at the morphological level. This study was carried out to assess the potential of early screening for discriminating ploidy and genome classes in 4x (AAAB)-2x (AA) breeding populations, based on flow cytometry and genome-specific RAPD analysis. Results indicate that progenies of 4x-2x crosses produced predominantly 3x progenies (94.1%). RAPD analysis identified seven genomic classes, dominated by AAA and AAB configurations segregating 1:1 (χ2 = 0.21, P = 0.05). Plant size and bunch weight increased with ploidy level, justifying ploidy-based grouping of progenies for homogenous field evaluation. Similarly, genome-based grouping within ploidy classes is recommended to allow proper evaluation of progenies according to targeted postharvest utilization. Thus, ploidy analysis by flow cytometry and genome determination by RAPD open prospects for enhancing breeding efficiency in the development of triploid bananas or plantains.